Identifying and recruiting language teachers : a research-based approach - Swanson, Peter B. (Emerald Publishing Limited : Information Age Pub., 2013)
This volume begins by locating critical inquiry within the epistemological and methodological history of second language study. Subsequent chapters portray researcher-participant exploration of identity and agency while challenging inequitable policies and practices. Research on internationalization, Englishization, and/or transborder migration address language policies and knowledge production at universities in Hong Kong, Standard English and Singlish controversies in Singapore, media portrayals of the English as an Official Language movement in South Korea, transnational advocacy in Japan, and Nicaraguan/Costa Rican South to South migration. Transnational locations of identity and agency are fore-fronted in narrative descriptions of Korean heritage language learners, a discursive journey from East Timor to Hawaii, and a reclaimed life history by a Chinese peasant woman. Labor union and GLBT legal work illustrate discourses that can hinder or facilitate agency and change. Hawaiian educators advocate for indigenous self-determination through revealing the political and social meanings of research. California educators describe struggles at the front-lines of resistance to policies and practices harmful to marginalized children. A Participatory Action Research (PAR) project portrays how Latina youth in the U.S. "resist wounding inscriptions" of the intersecting emotional and physical violence of homes, communities, and antiimmigrant policies and attitudes. Promoting agency through drawing on diversity resources is modeled in a bilingual undergraduate PAR project. The volume as a whole provides a model for critical research that explores the multifaceted and evolving nature of language identities while placing those traditionally known as participants at the center of agency and advocacy.